Forage Report 2015 - J. D. Holman; Jane Lingenfelser; A. Obour; A. Esser; J. L. Moyer; G. Cramer; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2017)
In 2015 summer annual forage variety trials were conducted across Kansas near Garden City, Hays, Hutchinson, Mound Valley, and Scandia. All sites evaluated hay and silage entries, except Hutchinson, which only evaluated hay entries. Companies were able to enter varieties into any possible combinations of research sites, so not all sites had all varieties. Across the sites, a total of 30 hay varieties and 22 silage varieties were evaluated.
Keywords: Forage